The analysis of echelon usage control and evaluation indexes of helicopters - HAO Wanliang; WANG Zhanyuan; LIU Chao (Hangkong gongcheng jinzhan, 2023)
The echelon usage control of helicopters is one of the most import job in the aviation equipment support,the overall efficiency of helicopter can be maximized by arranging the echelon usage. Aiming at the difficulty and lack of evaluation index in the echelon usage control, two methods of the echelon usage control are introduced, the way of echelon optimization control technology is mainly expatiated, the influences of different parameters in the echelon usage control are deduced and analyzed, and three evaluation indexes of echelon usage control are presented. Finally, a case study is carried out by using the method of echelon optimization technology, the results indicate that the sum of minimum time and maximum time of annual mission is a constant, the parameter selection method deduced in the paper is correct, and the evaluation indexes proposed are reasonable, and the research direction of the next step is clarified.